Pemberdayaan Ekonomi Perempuan melalui Edukasi dan Produksi Pembalut Kain yang Aman dan Ramah Lingkungan - Prabawanti, Benedicta Evienia; Wijaya, Celine Putri; Rimananda, Gabriella Lintang; Agustian, Murniati; Sanie, Susy (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Community service is an activity with a community empowerment program implemented by lecturers and students of Atma Jaya Catholic University Indonesia. The target partners in this activity are female members of the Bogor Cathedral Church who have limited knowledge as common people about the dangers of disposable sanitary pads for reproductive health as well as the environment and in need of entrepreneurial activities to improve the family economy. The purpose of this activity is to educate women about reproductive health and healthy menstrual cycles as well as empowering the production of safe and environmentally friendly sanitary pads to improve their income. The method used in this activity is education and training as a concrete step in realizing the objectives of this activity and achieving the target in real terms. The results obtained from this activity are increasing the awareness of female partners about the importance of maintaining reproductive health and the women's body and the creation of a website that is in the development stage as an education facility and purchasing the production of cloth sanitary pads.